Viewing Instructions Accompanying Action Observation Modulate Corticospinal Excitability - Wright, David J.; McCormick, Sheree A.; Williams, Jacqueline; Holmes, Paul S. (Frontiers in Human Neuroscience, 2016)
Action observation interventions may have the potential to contribute to improved motor function in motor (re)learning settings by promoting functional activity and plasticity in the motor regions of the brain. Optimal methods for delivering such interventions, however, have yet to be established. This experiment investigated the effect on corticospinal excitability of manipulating the viewing instructions provided to participants (N = 21) prior to action observation. Specifically, motor evoked potential responses measured from the right hand muscles following single-pulse transcranial magnetic stimulation to the left motor cortex were compared when participants were instructed to observe finger-thumb opposition movement sequences: (i) passively; (ii) with the intent to imitate the observed movement; or (iii) whilst simultaneously and actively imagining that they were performing the movement as they observed it. All three action observation viewing instructions facilitated corticospinal excitability to a greater extent than did observation of a static hand. In addition, the extent to which corticospinal excitability was facilitated was greater during combined observation and imagery, compared to passive observation. These findings have important implications for the design of action observation interventions in motor (re)learning settings, where instructions that encourage observers to simultaneously imagine themselves performing the observed movement may offer the current optimal method for improving motor function through action observation.